BARITO RIVERSIDE PUBLIC OPEN SPACE IN MUARA TEWEH CITY - Farhani, Muhammad Reza; Heldiansyah, J. C. (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Regional Government of North Barito Regency carried out an image of Muara Teweh City with the titles